Acoustic Rehabilitation of the Church of Santa Ana in Moratalaz, Madrid - BUENO, Ana Marıa; LEÓN, Angel Luis; GALINDO, Miguel (Archives of Acoustics, 2012)
The church of Santa Ana in Moratalaz, Madrid, Spain (1965–1971), is an emblematic work of the architect Miguel Fisac. In his long career include interventions in the religious field, constituting one of the most important contributions to Spanish religious architecture of the last century. This church is a singular place of worship and architecturally significant, in which the acoustics played an important role in the configuration of the spatiality of the church. This paper studies the acoustic behaviour of the church and its relationship with its unique structural, spatial and coating material characteristics. The analysis of the current acoustic conditions, with high reverberation times (up to 6 seconds) and poor intelligibility on the audience, serve as the basis for making an acoustic rehabilitation proposal that contributes to improving the sound conditions of the building for the intended use, without distorting the spatial, formal and material aspects with which the architect conceived the project.